Analisis Dampak Ekonomi dan Strategi Pengembangan Wisata Kali Kembar Kabupaten Probolinggo - Muh Hamzah; Adinda Medi Silvia; Anisa Nava Tidar (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
This study aims to analyze the economic impact of the Kali Kembar tourist destination on the community of Gading Wetan Village, Probolinggo Regency, and to formulate sustainable development strategies. Kali Kembar, as a local ecotourism potential, has begun to attract regional visitors, yet its management remains suboptimal. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and document analysis. The findings reveal that the tourism site has brought positive economic impacts, including increased household income, the emergence of new business opportunities, and the circulation of the local economy through the informal sector. However, institutional management, infrastructure development, and promotional efforts remain key challenges. Proposed development strategies include strengthening the institutional capacity of tourism managers, enhancing facility quality and accessibility, developing attractions based on local wisdom, and fostering synergy between the village government and local entrepreneurs. This study recommends a community-based tourism development model as the primary approach to promote economic, social, and environmental sustainability in the area.